ВИДЫ И ОПИСАНИЕ МЕТОДОВ, ИСПОЛЬЗУЕМЫХ В УПРАВЛЕНИИ ПРОЕКТАМИ (Журнал «Маркетинг», 2025)
The practical application of project management requires the use of specific methods. In construction production, project management plays a crucial role, as organizing construction processes involves ensuring the alignment of deadlines, quality, and cost—an inherently complex task. This article explores widely used project management approaches and outlines their characteristics.
Keywords: проектное управление; традиционные и гибкие методы; критический путь; Waterfall; Agile; методы управления потоками